EMERGENCY OBSTETRIC CARE AVAILABILITY, ACCESSIBILITY AND UTILIZATION IN EIGHT DISTRICTS IN PAKISTAN'S NORTH WEST FRONTIER PROVINCE - Ali, Moazzam; Ayaz, Mohammad; Rizwan, Humayun; Hashim, Saima; Kuroiwa, Chushi (Journal of Ayub Medical College Abbottabad, 2006)
Introduction: Reducing maternal mortality is a critical issue in Pakistan. Do public health care centers in Pakistan's North West Frontier Province (NWFP) comply with minimum UN recommendations for availability, use, and quality of basic and comprehensive Emergency Obstetric Care (EmOC) as measured by UN process indicators? Methods : All public health facilities providing EmOC (n=50) in 30% of districts in NWFP province (n=8 districts) sampled randomly in September 2003 were included in a cross-sectional study. Data came from health facility records. Results: Almost all indicators were below minimum recommended UN levels. The number of facilities providing basic EmOC services was much too low to be called providing comprehensive coverage. A low percentage of births took place in hospital and few women with complications reached EmOC facilities. Caesarean section was either underutilized or unavailable. The case fatality rate was low, perhaps due to poor record-keeping. Conclusion: The findings of this first needs assessment in NWFP province can serve as a benchmark for monitoring future progress. In resource-poor countries like Pakistan, it is important to upgrade existing facilities, giving special emphasis to facilities that provide basic EmOC services, since many problems can be resolved at the most basic level. Health policy makers and planners need to take immediate, appropriate rectifying measures to, inter alia, improve staffing in rural areas, enhance staff skills through training, upgrade management and supervision, ensure medical supply availability, mandate proper record-keeping, and observe progress by monitoring process indicators regularly. Key Words: EmOC services, Process indicators, Mental Mortality, Public Hospital, Pakistan.